1966
DOI: 10.1161/01.cir.34.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Level of Blood Pressure Measured Casually and by Portable Recorders and Severity of Complications in Essential Hypertension

Abstract: the relationship between the level of arterial blood pressure and the development of hypertensive complications is one of the conspicuous difficulties in current concepts of the natural history of essential hypertension. That cardiovascular complications of hypertension are generally more prevalent with the higher levels of blood pressure is recognized. Published data, 1-3 however, invariably include a substantial proportion of cases in which casual blood pressures* were considerably elevated, yet hypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
7

Year Published

1976
1976
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(141 citation statements)
references
References 20 publications
4
129
0
7
Order By: Relevance
“…Although this has previously been demonstrated in 1966 by Sokolow et al 9 and has been confirmed by other studies assessing targetorgan disease in the heart, kidneys, brain and blood vessels, [11][12][13][14][15] according to the data presented here, the relationship between criteria of left ventricular mass and blood pressure in a selection of treated hypertensive patients is weak (at most 0.28). This is in contrast with the relationship found in studies including subjects with a wide spectrum of blood pressure values, including normotensive and untreated hypertensive subjects (correlation coefficients up to 0.56).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although this has previously been demonstrated in 1966 by Sokolow et al 9 and has been confirmed by other studies assessing targetorgan disease in the heart, kidneys, brain and blood vessels, [11][12][13][14][15] according to the data presented here, the relationship between criteria of left ventricular mass and blood pressure in a selection of treated hypertensive patients is weak (at most 0.28). This is in contrast with the relationship found in studies including subjects with a wide spectrum of blood pressure values, including normotensive and untreated hypertensive subjects (correlation coefficients up to 0.56).…”
Section: Discussionsupporting
confidence: 82%
“…[9][10][11][12][13][14][15] In addition, single office blood pressure only weakly predicts coronary events. [9][10][11][12][13][14][15] However some of these studies have been criticised in terms of trial design. 16,17 Furthermore with regards to the development of target organ damage, controversy exists regarding the relative importance…”
Section: Introductionmentioning
confidence: 99%
“…ECG-LVH was diagnosed on the basis of increased voltage with or without repolarization abnormality (strain pattern). 16 Data were analysed using an IBM-compatible computer incorporating the Statistical Package for Social Sciences (SPSS/PC+). Mantel-Haenszel chisquared tests were used to assess the differences between categories of patients.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between values from these two measurement modalities is relatively low with reported coefficients of correlation around 0.5-0.7. [1][2][3] It is unsolved which measure is 'true', ie, which best reflects the 'usual' BP and prognosis. 4 The lack of identity between the two methods of measurement yields a group of patients with the combination of hypertensive office BP and normal ambulatory BP (ABP), which is generally referred to as 'white coat hypertension'.…”
Section: Introductionmentioning
confidence: 99%